MN and DY doped strontium aluminate'soptical properties- a comparative study. (2021) - Jisha, V.T.; Meera, M.R.
Abstract: Through sol gel method Mn and Dy doped Strontium aluminate phosphors prepared. The prepared phosphors has been characterized by Powder X-ray diffraction, Scanning electron microscope. Optical properties were carried out by photoluminescence analysis. Photoluminescence studies of the prepared phosphors showed prominent IR emission, green emission and UV emission. To investigate the reaction that took place in the process of sample preparation, simultaneous TG–DSC testing was conducted from room temperature to 1000˚C.